FACTORS INFLUENCING THE VULNERABILITY OF ROAD INFRASTRUCTURE TO WILDFIRES - Tsekova, Mariana (E-Journal VFU, 2025)
The increase in the number of forest fires and their impact on road infrastructure necessitates the search for methods to increase the resilience and susceptibility of roads to fires. The factors that influence forest fires are environmental, climatic, human activity, due to the use of vulnerable materials. Proactive measures are proposed to reduce the vulnerability of road infrastructure to forest fires. Methods to improve post-fire recovery are indicated.
Keywords: wildfires; resilience of road infrastructure; post-fire recovery